TOXIGENIC MOLDS ON FISH FEEDS-I: IMPACT OF CLIMATIC FACTORS - DAS, MEENAXI; PRASAD, SHAMBHU; VERMA, SHISHIR K. (Journal of Indian Fisheries Association, 2015)
The present communication is a survey report carried out to assess the incidence of toxic mycoflora on seven types of agriculture products/byproducts incorporated during fish culture as supplementary dietary items. Samples were obtained from various sources at Darbhanga, Madhubani and Samashtipur districts during summer, winter and monsoon months. Out of the total 177 4 samples, only 894 appeared to be fresh visually reflecting average incidence of contamination around 46.6%. However, the apparently fresh samples, when subjected to culture, 26.9% of them were found to be contaminated. Thus, degree of fungal spoilage in feed ingredients in parts of north Bihar appears to be significantly high (73.5%). The present study illustrates the facts with special reference to Aspergillus flavus, A parasiticus (elaborating aflatoxins) A. ochraceous, Penicilium viradicatum (elaborating ochratoxins) andAversicolor (elaborating sterigmatocystin). The other strains already known for their toxigenic potentials that appeared on the present substrates included A. niger, A. fumigatus, A. candidus, P. islandicum, Rhizopus spp. and Mucur spp. Studies indicate that the prevelent climatic factors like temperature and relative humidity facilitate a congenial condition almost all through the year and in particular during summer and monsoon months. But water content of the substrates is a vital factor that further accelerates the pace of mycobial spoilage. A thorough sun-drying of the agricultural commodities before prolonged storage to bring water content below the ’’low risk limit" may significantly reduce the incidence of molds. Keywords : Toxigenic molds, fish feeds, fungal spoilage